ACTIVITIES OF NATIONAL CULTURAL CENTERS IN UZBEKISTAN - Sirojiddin Sharofov Jaloliddinovich (American Journals Publishing, 2023)
National cultural centers of Uzbekistan play an incomparable role in preserving and promoting the country's rich cultural heritage. These centers serve as hubs for various events celebrating the various traditions, arts and customs of Uzbekistan. Let us explore the important activities carried out by these centers.
Keywords: National cultural centers, Article 19, Thought and practice, artists, crafts.